2015
DOI: 10.1128/aac.04742-14
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy-α-Lapachone Has In Vitro and In Vivo Anti-Leishmania (Leishmania) amazonensis Effects and Inhibits Serine Proteinase Activity in This Parasite

Abstract: Leishmania (Leishmania) amazonensis is a protozoan that causes infections with a broad spectrum of clinical manifestations. The currently available chemotherapeutic treatments present many problems, such as several adverse side effects and the development of resistant strains. Natural compounds have been investigated as potential antileishmanial agents, and the effects of epoxy-␣-lapachone on L. (L.) amazonensis were analyzed in the present study. This compound was able to cause measurable effects on promastig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Specifically a naphthoquinone derivative epoxy-α-lapachone that showed efficiency on L. amazonensis in vitro and in vivo, which mechanism suggested is associated to the inhibition of oligopeptidase B, a serine proteinase from Leishmania spp. , 2015.…”
Section: Introductionmentioning
confidence: 95%
“…Specifically a naphthoquinone derivative epoxy-α-lapachone that showed efficiency on L. amazonensis in vitro and in vivo, which mechanism suggested is associated to the inhibition of oligopeptidase B, a serine proteinase from Leishmania spp. , 2015.…”
Section: Introductionmentioning
confidence: 95%
“…As this compound is also derived from the α-lapachone molecule by an epoxidation reaction, and shares most of chemical and structural features with epoxy-α-lapachone, is possible that the new oxirane also acts by inhibiting proteases from Leishmania sp. and other trypanosomatids, as previously reported [ 12 , 14 , 20 , 21 ], however further studies are needed to prove this hypothesis.…”
Section: Discussionmentioning
confidence: 58%
“…We have demonstrated that epoxy-α-lapachone was capable to kill promastigote forms of Leishmania ( Viannia ) braziliensis and Leishmania ( Leishmania ) amazonensis and intracellular amastigotes in human macrophages [ 13 ]. Furthermore, reduction of the lesion size in the paw of BALB/c mice infected was observed after four weeks of treatment [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have demonstrated that LAP and LAW (Fig. 1), were effective against Leishmania in both in vitro and in vivo experimental infections and showed low toxicity for mammalian cells (Oliveira et al, 2018; Souza-Silva et al, 2014, 2015).
Fig.
…”
Section: Introductionmentioning
confidence: 99%